On the development of markers for pathological TDP-43 in amyotrophic lateral sclerosis with and without dementia - BOKDE, ARUN LAWRENCE WARREN; BEDE, PETER; HAMPEL, HARALD; HARDIMAN, ORLA (Elsevier, 2011)
Pathological 43-kDa transactive responsive sequence DNA-binding protein (TDP-43) has been recognized as the major disease protein in amyotrophic lateral sclerosis (ALS), frontotemporal lobar degeneration with ubiquitin positive, tau and ?-synuclein negative inclusions (FTLD-U) and the transitional forms between these multisystem conditions. In order to develop TDP-43 into a successful ALS biomarker, the natural history of TDP-43 pathology needs to be characterized and the underlying pathophysiology established. Here we propose a spatial and temporal ?two-axis? model of central nervous system vulnerability for TDP-43 linked degeneration and discuss recent studies on potential biomarkers related to pathological TDP-43 in the cerebrospinal fluid (CSF), blood, and skeletal muscle. The model includes the following ?two arms?: First, a ?motor neuron disease? or ?spinal cord/brainstem to motor cortex? axis (with degeneration possibly ascending from the lower motor neurons to the upper motor neurons); and secondly, a ?dementia? or ?corticoid/allocortical to neocortex? axis (with a probable spread of TDP-43 linked degeneration from the mediotemporal lobe to wider mesocortical and neocortical brain areas). At the cellular level, there is a gradual disappearance of normal TDP-43 in the nucleus in combination with the formation of pathological aggregates in the cell body and cellular processes, which can also be used to identify the stage of the disease process. Moreover, TDP-43 lesions in subpial/subependymal or perivascular localizations have been noted in TDP-43 linked neurodegeneration, and this might account for increased CSF and blood TDP-43 levels through mechanisms that remain to be elucidated.
PUBLISHED
Keywords: Neuroscience; Amyothrophic lateral sclerosis